Unravelling the Cu-Co nanoparticle synergy over Ceria-Zirconia support toward efficient reverse water gas shift (RWGS) conversion under H2 lean conditions - Jagtap, Anuradha Vijay; Bamnia, Mahesh Kumar; Maibam, Ashakiran; Bajpai, Jyotsna Paliwal; Gupta, Sharad; Thomas, Sharon K.; Dabke, Niteen B.; Vinod, C. P. (Chemical Engineering Journal, 2025)
CO2 emissions leading to global warming and environmental and socio-economic issues have propelled the research community to develop technologies capable of capturing and converting CO2 into valuable products. Controlling the selectivity toward platform molecules like CO, methanol, or methane is a fundamental challenge in CO2 hydrogenation. Supported cobalt nanoparticles are known for hydrocarbon production through FischerTropsch (FT) reaction, and Cu-based catalysts are known for reverse water gas shift (RWGS) reaction. Here, we show that d-band centre can be carefully modulated by making bimetallic combinations of Cu and Co for a highly active RWGS catalyst. An oxygen vacancy-rich nanostructured ceria-zirconia (CZ) support with Cu nanoparticles (2 wt%) modified with as low as 0.05 wt% Co shows excellent conversion for CO2 hydrogenation and selectivity for CO below 500 degrees C. The optimized catalyst shows CO2 conversion even under hydrogen lean conditions (H2/ CO2 ratio 0.5:1), with a breakthrough rate of 206023 mmol/gmetal/h for CO at 600 degrees C, having H2 utilization of 80% for the RWGS process.
Keywords: Bimetallic catalyst; Ceria-zirconia; CO 2 hydrogenation; Cobalt catalyst; Copper catalyst; Reverse water gas shift (RWGS); synergistic effect